Envenomation cases reporting to a rural primary health care center in Maharashtra - Deshpande, Swati; Pathak, Barsha; Rahini, S.; Mecca, Rukman (International Journal Of Community Medicine And Public Health, 2018)
Background: Annually in the world 1,200,000 cases of envenomation and 3,250 deaths by scorpion stings ensue. Alarming statistics are also seen for snake bites globally i.e. 421,000 envenoming and 20,000 deaths. India is the country with the highest annual number of envenoming (81,000) and deaths (nearly 11,000). Methods: A retrospective cross-sectional study based on hospital record to assess the trend of diverse cases of scorpion sting and snake bite reporting to a rural primary health care center from January 2017 to December 2017. A pre-designed case record proforma was utilized to estimate the percentages of diverse cases of scorpion and snake bites attending the center and assess the demographic profile of the bite cases along with the evaluation of management protocol of these bite cases. Results: 190 cases of envenomation visited the health care center in a year where 165 were scorpion stings and 25 were snake bites. Referral to higher centres for management was established to be more in children and adolescent age groups but the mean age of envenomation was evaluated to be 33.8 years. Remarkable seasonal variation in the envenomation cases was spotted. Anti-snake venom was used for treatment of snake bites but anti-venom was not utilized for scorpion bites. Conclusions: Envenomation cases were common in adults but complications were higher in children and adolescents. We observed gender based risk and a seasonal incidence of envenomation. Most patients of envenomation were successfully managed in rural hospital with limited facilities.